Radiotherapy for Oligometastatic Lung Cancer - Bergsma, Derek P.; Salama, Joseph K.; Singh, Deepinder P.; Chmura, Steven J.; Milano, Michael T. (Frontiers in Oncology, 2017)
Non-small cell lung cancer (NSCLC) typically presents at an advanced stage, which is often felt to be incurable, and such patients are usually treated with a palliative approach. Accumulating retrospective and prospective clinical evidence, including a recently completed randomized trial, support the existence of an oligometastatic disease state wherein select individuals with advanced NSCLC may experience historically unprecedented prolonged survival with aggressive local treatments, consisting of radiotherapy and/or surgery, to limited sites of metastatic disease. This is reflected in the most recent AJCC staging subcategorizing metastatic disease into intra-thoracic (M1a), a single extra thoracic site (M1b), and more diffuse metastases (M1c). In the field of radiation oncology, recent technological advances have allowed for the delivery of very high, potentially ablative, doses of radiotherapy to both intra- and extra-cranial disease sites, referred to as stereotactic radiosurgery (SRS) and stereotactic body radiotherapy (SBRT or SABR), in much shorter time periods compared to conventional radiation and with minimal associated toxicity. At the same time, significant improvements in systemic therapy, including platinum-based doublet chemotherapy, molecular agents targeting oncogene-addicted NSCLC and immunotherapy in the form of checkpoint inhibitors, have led to improved control of micro-metastatic disease and extended survival sparking newfound interest in combining these agents with ablative local therapies to provide additive, and in the case of radiation and immunotherapy, potentially synergistic, effects in order to further improve progression free and overall survival. Presently, despite the tantalizing potential associated with aggressive local therapy in the setting of oligometastatic NSCLC, well designed prospective randomized controlled trials sufficiently powered to detect and measure the possible added benefit afforded by this approach are desperately needed.